Large Energy Q-Switched Fiber Laser With Black Phosphorus Saturable Absorber Fabricated by Sol−Gel Technique - Zhendong Chen; Tianyu Liu; Duo Pan; Yonggang Wang; Yajun Li; Jianjun Wu (IEEE Photonics Journal)
Black phosphorus (BP) has attracted extensive attention due to its unique optical and electrical properties. However, BP is easily oxidized in the air, which significantly limits its application. In this study, BP is successful doped into sol-gel glass, it shows excellent chemical stability in atmospheric environment for five months. In addition, as a kind of inorganic matrix, optical damage threshold of BP-doped sol-gel glass reaches as high as 51.69 GW/cm2, which is six times higher than that of plastic polymer. Saturable absorption parameters of the BP are maintained after five months in the air. The BP-doped sol-gel glass is inserted into erbium-doped fiber (EDF) laser to realize passively Q-switched and mode locked operation. Compared to most Q-switched EDF lasers based on broadband absorbers, the single pulse energy is one of the highest values (315.99 nJ). Overall, these data evidently provide a practical solution to stabilize BP in the air by embedding it in the silica, and also open the way for extensive applications of BP.